2014
DOI: 10.1175/jcli-d-14-00438.1
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnections between Tropical Pacific SST Anomalies and Extratropical Southern Hemisphere Climate

Abstract: Teleconnections from tropical Pacific sea surface temperature (SST) anomalies to the high-latitude Southern Hemisphere (SH) are examined using observations and reanalysis. Analysis of tropical Pacific SST anomalies is conducted separately for the central Pacific (CP) and eastern Pacific (EP) regions. During the austral cold season, extratropical SH atmospheric Rossby wave train patterns are observed in association with both EP and CP SST variability. The primary difference between the patterns is the westward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 48 publications
9
61
0
Order By: Relevance
“…5c, hatching), have moved toward the central Pacific. Consistent with the observational analyses of Ciasto et al (2015), such shifts may explain the more eastward location of South Pacific Z 200 anomalies.…”
Section: Model Atl3 Teleconnectionssupporting
confidence: 79%
See 2 more Smart Citations
“…5c, hatching), have moved toward the central Pacific. Consistent with the observational analyses of Ciasto et al (2015), such shifts may explain the more eastward location of South Pacific Z 200 anomalies.…”
Section: Model Atl3 Teleconnectionssupporting
confidence: 79%
“…In both cases, significant geopotential height anomalies are observed over the Atlantic and Pacific Oceans, but with enhanced magnitudes in the respective basin. Atlantic anomalies are characterized by contrasting pressure centers between the subtropics and midlatitudes, while Pacific anomalies represent the high-latitude response to ENSO; a wave train that appears as positive pressure anomalies over the subtropical Pacific, negative pressure anomalies over the ASL, and positive pressure anomalies over Antarctica, resembling the seasonal teleconnections observed in several studies (e.g., Simpkins et al 2012;Ciasto et al 2015). This Pacific-centered pattern shall be termed ''ENSO-like.''…”
Section: B Comparison Of Observed Atlantic and Pacific Teleconnectionsmentioning
confidence: 85%
See 1 more Smart Citation
“…The positive phase of the PSA is known to be related to La Niña and the negative phase of the PSA is related to El Niño (e.g., Mo 2000). Previous studies showed that ENSO, together with various phases of the SAM and the PSA, can influence the Southern Ocean SSTs (e.g., Ciasto and Thompson 2008;Lee et al 2010;Yeo and Kim 2015), Antarctic sea ice concentrations (e.g., Liu et al 2004;Stammerjohn et al 2008;Yuan and Li 2008), and Antarctic surface air temperatures (e.g., Kwok and Comiso 2002;Ding et al 2011). Fogt and Bromwich (2006) found that the ENSO influences on the SH strengthened from the 1980s to the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and McPhaden (2010) suggested that the more frequent occurrence of CP El Niño has contributed to the SST warming trend in the tropical central Pacific. Several recent studies have begun to examine the possible different impacts of the two types of ENSO on the SH climate using observations (Hurwitz et al 2011;Song et al 2011;Sun et al 2013;Ciasto et al 2015) and model simulations (Zubiaurre and Calvo 2012;Hurwitz et al 2013;Lim et al 2013;Wilson et al 2014).…”
Section: Introductionmentioning
confidence: 99%